Think twice: exploring the effect of reflective practices with peer review on reflective writing and writing quality in computer-science education. Issue 4 (4th July 2019) - Demmans Epp, Carrie; Akcayir, Gokce; Phirangee, Krystle
ABSTRACT: Reflective writing is a proven way to increase the quality of learning and knowledge construction. However, its use in computer science education has received little attention. In this mixed-methods study, we investigated the effect of reflective writing practices, including peer review, on students' reflective writing and writing quality scores in a computer science education context. Three reflective writing assignments were required in a Human Computer Interaction course and two peers reviewed each assignment to give feedback. Rubrics were used to measure the reflective writing and writing quality characteristics of student work, and a peer feedback coding scheme was used to determine the characteristics of the feedback students provided to one another. Results revealed that students' reflective writing and writing quality did not differ across projects and they offered solutions as their most common type of feedback. Our results revealed further studies need to keep investigating new approaches in terms of timing, guidelines, and supportive tools to promote reflective writing to determine which activity designs facilitate student improvement.